Membrane physical properties influence transmembrane helix formation - Barrera, Francisco N. (National Academy of Sciences, 2012)
The pHLIP peptide has three states: (I) soluble in aqueous buffer, (II) bound to the bilayer surface at neutral pH, and (III) inserted as a transmembrane (TM) helix at acidic pH. The membrane insertion of pHLIP at low pH can be used to target the acidic tissues characteristic of different diseases, such as cancer. We find that the α-helix content of state II depends on lipid acyl chain length but not cholesterol, suggesting the helicity of the bound state may be controlled by the bilayer elastic bending modulus. Experiments with the P20G variant show the proline residue in pHLIP reduces the α-helix content of both states II and III. We also observe that the membrane insertion pKa is influenced by membrane physical properties, following a biphasic pattern similar to the membrane thickness optima observed for the function of eukaryotic membrane proteins. Because tumor cells exhibit altered membrane fluidity, we suggest this might influence pHLIP tumor targeting. We used a cell insertion assay to determine the pKa in live cells, observing that the properties in liposomes held in the more complex plasma membrane. Our results show that the formation of a TM helix is modulated by both the conformational propensities of the peptide and the physical properties of the bilayer. These results suggest a physical role for helix-membrane interactions in optimizing the function of more complex TM proteins.